Military chemical warfare agent human subjects testing: part 1--history of six-decades of military experiments with chemical warfare agents. - Brown M; Brown, Mark (Military Medicine, 2009)
Military chemical warfare agent testing from World War I to 1975 produced thousands of veterans with concerns of possible long-term health consequences. Clinical and research evaluation of potential long-term health effects has been difficult because the exposures occurred decades ago, the identity of troops exposed and exposure magnitudes are uncertain, and acute effects during experiments poorly documented. In contrast, a companion article describes the large amount of information available about the specific agents tested and their long-term health effects. This short history describes U.S. military chemical-agent experiments with human subjects and identifies tested agents. Finally, the demonstrated need to anticipate future health concerns from military personnel involved in such military testing suggests current and future military researchers should be required, by law and regulation, to fully record the identity of those exposed, relevant exposure magnitude, and complete medical information for all subjects. New study protocols and institutional review board approvals for research involving military personnel should reflect this need.